(untitled) (Journal of Plant Disease Sciences, 2025)
The current study was conducted to investigate the effect of culture media, atmospheric temperature, and relative humidity on the growth and development of Pythium deliense causing damping-off in acid lime.A total of six solid culture media—Oat Meal Agar, Corn Meal Agar, Martin’s Rose Bengal Agar, V8 Juice Agar, Malt Extract Agar, and Potato Dextrose Agar—were tested for fungal growth. Among these, Oat Meal Agar, Corn Meal Agar, and Martin’s Rose Bengal Agar were found to be the most suitable, with a maximum radial growth of Pythium deliense (90.0 mm), while the least growth was recorded on Potato Dextrose Agar (27.56 mm).The colony characteristics of Pythium deliense varied across media, exhibiting white-colored, evenly thick to sparse growth with floral patterns. The fungus produced aseptate mycelium and globose-shaped sporangia.Physiological studies revealed that the fungal growth significantly varied with different temperature and relative humidity levels. The optimal growth of Pythium deliense was recorded at 25°C and >85% relative humidity.Acid lime (Citrus aurantifolia Swingle) is an important horticultural crop in various regions, including Akola and Amravati districts, where damping-off disease significantly reduces crop yield and quality.